Comparative Efficacy of Different Drugs for Lower Urinary Tract Symptoms due to Benign Prostatic Hyperplasia: A Bayesian Network Meta-Analysis - Fan, Zhinan; Shi, Hongjin; Zhang, Jinsong; Wang, Haifeng; Wang, Jiansong (Frontiers in Pharmacology, 2022)
Background: Lower urinary tract symptoms (LUTS) caused by benign prostatic hyperplasia (BPH) are common in middle-aged and elderly men. The current drugs for treating this disease include α1-adrenoceptor antagonists (ABs), muscarinic receptor antagonists (MRAs), phosphodiesterase 5 inhibitors (PDE5-Is), and β3-adrenoceptor agonists (B3As). However, direct comparative studies analyzing different therapies are limited; therefore, we conducted a network meta-analysis (NMA) to evaluate the efficacy of different drug regimens for treating BPH/LUTS. Methods: The PubMed, EMbase, Web of Science, and Cochrane Library databases were searched to collect randomized controlled trials (RCTs) of different drug treatments for BPH/LUTS from January 2000 to April 2021. The NMA was performed using R 4.1 software. Results: Fifty-five RCTs were included among a total of 1639 trials. ① ABs+PDE5-Is, ABs+ B3As, ABs+MRAs, ABs, and PDE5-IS were superior to the placebo in improving the total International Prostate Symptom Score (IPSS), IPSS-Voiding, and IPSS-storage. ② For increasing the maximum flow rate (Qmax), ABs+ PDE5-Is, ABs+MRAs, and ABs were more effective than the placebo. ③ Regarding reducing post-void residual urine (PVR), none of the six treatment plans had significant effects. Conclusion: Combination therapy showed greater efficacy than monotherapy, and ABs+PDE5-Is was the most successful treatment for improving the overall IPSS score. ABs are a primary therapeutic measure to increase Qmax, and ABs+PDE5-I may be a more suitable choice for enhancing Qmax. The combination of MRA and AB + MRA may lead to an increase in PVR.